Students’ Perception On The Use Of Comic Strips: Reading Skill - Harahap, Tsabita Ananda; Suryaman, Maman (Jurnal Ilmiah Mandala Education (JIME), 2022)
The main objective of this study was to analyze the perception students in Senior High School which discussed about the use of comic strips in students’ reading comprehension. This study involved the descriptive quantitative method data deriving from questionnaires. The instruments aimed to get feedback from the students about their perception about this topic. The finding show the students take the media positively and also help them in understanding the text using comic strip rather than text only because they can use their imagination to developing their critical thinking skill and comic strip also enjoyable to be the tool for their learning process.